Performance Evaluations Are Not Legitimacy Judgments: A Caution About Interpreting Public Opinions Toward the United States Supreme Court - James L. Gibson (Washington University Journal of Law & Policy, 2017)
This Article explains the differences between public opinion of the Supreme Court’s performance and its underlying legitimacy as an institution. Gibson identifies public perception of the Supreme Court as being influenced by partisan and ideological differences. The Article compares “performance evaluations” to “institutional legitimacy,” defined as a construct between authorities and how those connected to them do what they believe to be appropriate. Gibson concludes these separations must be recognized, particularly as the public itself becomes more ideologically polarized and such polarization may permeate the bench itself in the future.
Keywords: Supreme Court; Opinion; Judiciary; Performance; Legitimacy; Evaluations; Ideology; Study